Data Collection & Analysis (Technology) - Mohd Rashid, Ab Hamid (Penerbit UMP, 2017)
This module is specially tailored to assist postgraduate students of science, engineering and technology in data collection and analysis. The content in this module is primarily focused on the applications of various statistical techniques for quantitative and categorical data. Through this course, students are able to learn and directly apply the statistical knowledge in the research or problems being studied. This module provides examples to show connections between theory and application in scientific research. The materials in this module also integrate well with computer software packages i.e. Statistical Package for Social Sciences(SPSS)